2021
DOI: 10.1038/s41388-021-02073-0
|View full text |Cite
|
Sign up to set email alerts
|

G3BP2 regulated by the lncRNA LINC01554 facilitates esophageal squamous cell carcinoma metastasis through stabilizing HDGF transcript

Abstract: Metastasis is the leading cause of death of patients with esophageal squamous cell carcinoma (ESCC). Although an increasing number of studies have demonstrated the involvement of G3BP2 in several human cancers, how G3BP2 interacts with long noncoding RNAs and regulates mRNA transcripts in mediating ESCC metastasis remains unclear. In this study, we uncovered that G3BP2 was upregulated in ESCC. Further analysis revealed that upregulation of G3BP2 was significantly correlated with lymph node metastasis, depth of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…In our research, we find that ATB could directly bind to p53 and thus regulate the expression level. In a recent study, LINC01554 maintained the high G3BP2 expression in ESCC by protecting G3BP2 from degradation through ubiquitination also edified us the mechanism that lncRNA could bind to target gene and regulate that [ 29 ]. In addition, metformin induction remarkably upregulated p53 in VSMCs.…”
Section: Discussionmentioning
confidence: 99%
“…In our research, we find that ATB could directly bind to p53 and thus regulate the expression level. In a recent study, LINC01554 maintained the high G3BP2 expression in ESCC by protecting G3BP2 from degradation through ubiquitination also edified us the mechanism that lncRNA could bind to target gene and regulate that [ 29 ]. In addition, metformin induction remarkably upregulated p53 in VSMCs.…”
Section: Discussionmentioning
confidence: 99%
“…The lncRNA MIR22HG has also been suggested as a novel cancer prognostic biomarker acting through ceRNA ( Zhang C et al, 2020 ). Similarly, the lncRNAs NORAD, AGPG, DNM3OS, VESTAR, IRF1-AS and LINC01554 have strong potential for application in the diagnosis and treatment of esophageal cancer ( Zhang B. X et al, 2019 ; Huang et al, 2019 ; Liu Y et al, 2020 ; Wang Y et al, 2021 ; Jia et al, 2021 ; Zheng et al, 2022 ) ( Figure 1 ; Table 2 ).…”
Section: Non-coding Rna Regulation and Esophageal Cancermentioning
confidence: 99%
“…EMT-related lncRNA DDX11-AS1 facilitated ESCC process through targeting miR-30d-5p to regulate SNAI1/ZEB2 expression and Wnt/beta-catenin pathway [ 12 ]. LncRNA LINC01554 acted as a promoter of ESCC through regulating G3BP2/HDGF axis to enhance ESCC cell migration and invasion [ 13 ]. In brief, these studies confirmed that lncRNAs served as clinical therapeutic targets for human ESCC.…”
Section: Introductionmentioning
confidence: 99%